Ways to improve the reliability of vehicles electrics - Шевченко, Костянтин Леонідович; Бондарєв, Сергій Іванович (Technology audit and production reserves, 2013)
Electrics in modern vehicles is accompanied by significant electromagnetic fields, which in total harm strongly human health. To prevent electromagnetic radiation at the stage of designing and manufacturing of electrics one should increase the screening capacity of the body of a vehicle, use special protective guides for wires, and reduce the number of wires. All the measures contribute to rise in vehicle’s price. In our opinion, a promising way of solution of the problem is usage of single-wire scheme of connection of electrics. The following conditions should be fulfilled - all electrics connected to one power line of a vehicle; the second conductor is the body of a vehicle. As a result of research we have developed three methods for managing electrics using single-wire scheme: pulse-periodic, frequency, pulse-code. Practical implementation of the proposed methods provides a significant simplification of electrics control schemes, reduces material consumption and the cost of the control circuit of electrics and electronic elements. The function of the control unit can be performed by a computer.